Natural diterpenoids in dermatology: Multifunctional roles and therapeutic potential for skin diseases - Li, Chunlin; Ma, Minghua; Liu, Xin; Hu, Yue; Feng, Zhiguang; Zhang, Ruoxi; Wang, Zhenwei; Nian, Hua; Zhu, Jianyong (Phytomedicine (Stuttgart), 2025)
Skin disorders are a collection of prevalent and frequent illnesses that have significant impacts on daily life. Currently, a limited number of effective therapeutic drugs are available that fall far short of the clinical needs; most medications usually offer chronic alleviation instead of treatment. Diterpenoids are the main components of many plant essential oils, such as lemon oil, turpentine, peppermint oil and camphor oil. Most of these compounds are water insoluble, volatile, aromatic, and oily substances. This paper systematically introduces major skin illnesses in regular life, lists related diterpenoids and their clinical applications, and summarizes the current status of clinical research on related diterpenoids and their structural formulas. This review may increase the research focus on dermatological illnesses by providing helpful knowledge for individuals involved in drug research on this subject. A thorough review of the literature was conducted using the search parameters “diterpenoid,” “skin diseases,” “structure” and “pharmacological activity” to retrieve articles from the PubMed, Web of Science, ACS, Elsevier Science and Scopus databases. [Display omitted]